PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN IBU DALAM PENANGANAN BALITA TERSEDAK - Zuryaty Zuryaty; Mohammad Lutfi (NHM PRESS, 2021)
A toddler is a general term for children aged 1-3 years (toddler) and preschool children (3-5 years). At the age of under, five is the age under full parental supervision, because at this age there is a high risk of experiencing various life- threatening events, such as choking or aspiration of salty objects. Choking (Choking) is complete or partial obstruction of the airway due to an object, making it difficult for the victim to breathe, and causing oxygen deprivation. The cause of choking in toddlers is mostly caused by foreign objects around them, which are accidentally swallowed by the child. Aspiration of a foreign body (choking) in the airway is an emergency that requires immediate treatment. This is a result of a lack of knowledge which has an impact on the behavior of mothers in dealing with choking in toddlers. The purpose of this study is to determine the effect of education on the level of maternal knowledge about handling choking on toddlers at the Morpanden Posyandu, Pangeran Geddungan Village, Blega District, Bangkalan Regency. The method in this study used quantitative research with the Pre-experimental Design approach, with One-Group Pretest. -Posttest Design. The populations were 29 respondents. The technique used in sampling was purposive sampling. The results of statistical tests with the Wilcoxon signed-rank test showed ρ value of 0,000, which means the value of ρ value <0.05 (α). The conclusion that can be drawn is that there is an effect of health education on maternal knowledge of choking toddlers at the Morpanden Posyandu, Pangeran Geddungan Village, Blega District, Bangkalan Regency